Feodalisme Dalam Wajah Modern: Studi Atas Penguasaan Tanah oleh Korporasi di Indonesia - Siswanto, Heru; Tobing, Clara Ignatia; Maharani, Raden Roro Fadhillah Alifiah; Paruda, Varenzi Tristantino; Hariri, Mohammad Rafiq; Nuraini, Aisyah Afifah; Sari, Dwintya; Pramesti, Salsabila Ayu; Ahma, Caliesta Widi; Tiara, Amanda; Ibrahim, Muhammad; Zakiya, Nathan Luth (Media Hukum Indonesia (MHI), 2024)
The control of land by large corporations in Indonesia, such as PT Semen Indonesia in Rembang, PT Silva Inhutani Lampung in Mesuji, and PT Perkebunan Nusantara in North Sumatra, reflects a phenomenon of "modern feudalism". These corporations obtain government permits without adequate consultation with local communities, resulting in economic, social, and environmental injustices for indigenous peoples and small farmers. Conflicts often arise with intimidation and forced evictions. Economically, corporations transform traditional livelihoods into low-wage labor, restricting access to agricultural land and forests. The impacts include social isolation, community conflicts, and environmental damage like deforestation and water pollution. The government needs to tightly regulate corporate land control, ensure community participation, and enforce environmental laws for sustainability and protection of indigenous rights and natural resources.